Compression garments and cerebral blood flow: Influence on cognitive and exercise performance - Smale, B. A.; Northey, J. M.; Smee, D. J.; Versey, N. G.; Rattray, B. (European Journal of Sport Science, 2018)
This study aimed to describe the effect of compression garments on middle cerebral artery blood flow velocity (MCAv) in relation to cognitive and exercise performance whilst cycling. In a randomised-controlled-cross-over design, 15 well-trained male cyclists were recruited to participate in three identical trials wearing loose fitting shorts (control), low-grade, or medium-grade compression garments. The protocol involved four 8 min increments of cycling at 30%, 50%, 70%, and 85% maximal power output and a 4 km time-trial. Participants undertook a cognitive Stroop task at baseline and at the midpoint of each increment. MCAv was monitored with Transcranial Doppler Ultrasonography. Mean arterial pressure (MAP) and partial pressure of end-tidal CO2 (PetCO2) were measured throughout. MCAv, MAP, PetCO2, and reaction time of the complex Stroop task were influenced by exercise intensity, but not compression garments. Compression garments significantly affected cognitive accuracy in the complex Stroop task such that low-grade compression appeared to enhance cognitive accuracy in comparison to the control condition at the highest intensity (p = .010). Time-trial performance did not differ between the control (338.0 ± 17.3 s), low-grade (338.7 ± 18.7 s), or medium-grade (342.2 ± 19.3 s) conditions (p = .114). Compression garments did not affect MCAv during exercise or time-trial performance, but compression may be beneficial for improved cognitive accuracy during high-intensity exercise. Further research is required to elucidate the potential impact on cognitive performance.